Pemberdayaan Kelompok Wanita Tani dalam Ketahanan Pangan di Desa Padaan Kecamatan Pabelan Kabupaten Semarang - saipullah Hasan; Bifa Aulia; Taufiq Yudha Kusuma; Nafisah Fidda Roini; Tika Setyani (Da'wa Faculty IAIN Purwokerto, 2021)
The Sustainable Peasant Women’s Group (KWT) has an important role in maintaining food security. Through KWT, women can actively involve themselves in utilizing the potential of natural resources to develop food businesses. The purpose of this study is to find out how KWT empowerment strategies in building food security. This research was conducted in Padaan Village, Pabelan Subdistrict. This research uses descriptive qualitative methods. Data collection methods use observation and interviews. The data that has been collected is then described, analyzed, and validated. The theory of food security empowerment becomes a frame of mind in analyzing data findings in the field. The results showed that the empowerment strategy of the Peasant Women’s Group (KWT) was carried out by implementing a shrimp satay business center program, planting vegetables on yardland, recycling cloth waste into vegetable plots, and developing catering businesses. The existence of these programs has shown the active role of women to meet food needs independently and develop entrepreneurial productivity.